MPC polymer modified porous polymer membrane and composite proton exchange membrane
By modifying the porous polymer membrane MPC surface, the incompatibility problem of composite proton exchange membrane between extremely hydrophobic and hydrophilic materials is solved, and a high-strength and high conductivity composite proton exchange membrane is achieved, which improves the stability and safety of fuel cells.
Patent Information
- Application Number
- CN202510461080.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-11
- Publication Date
- 2025-07-11
AI Technical Summary
The existing composite proton exchange membranes have incompatibility between extremely hydrophobic porous polytetrafluoroethylene and hydrophilic perfluorosulfonic acid resin, resulting in interface defects and degradation of performance, especially when circulating under wet and dry conditions, which affects the stability and safety of fuel cells.
The porous polymer film was surface modified by 2-(methacryloyloxy)ethylphosphate choline (MPC), and the polymer film surface was activated by plasma treatment, and then composited with perfluorosulfonic acid resin to improve its hydrophilicity and compatibility.
The mechanical strength and conductivity of the composite proton exchange membrane are significantly improved, the durability and stability of the membrane are enhanced, and the performance of the fuel cell is improved.
Smart Images

Figure CN120300236A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery materials, and particularly to a porous polymer membrane modified by MPC polymer and a composite proton exchange membrane. Background Art
[0002] A proton exchange membrane (PEM) is a key material for proton exchange membrane fuel cells. An ideal proton exchange membrane needs to have good chemical durability and mechanical durability. Initially, perfluorosulfonic acid resin was mostly used to prepare proton exchange membranes. However, this material is expensive and has low inherent strength, with certain limitations. In related technologies, Gore further proposed a composite proton exchange membrane using a porous polytetrafluoroethylene membrane as a reinforcing layer, which reduced the cost of the proton exchange membrane and improved its mechanical properties. However, porous polytetrafluoroethylene has strong hydrophobicity, while perfluorosulfonic acid resin is a strongly hydrophilic material, and the combination of the two has instability and may tear and delaminate under harsh conditions. Therefore, the composite PEM made of the two has problems such as reduced durability and potential safety hazards.
[0003] Therefore, there is an urgent need to provide a modified polymer membrane that can be tightly combined with perfluorosulfonic acid resin to improve the performance of the composite proton exchange membrane. Summary of the Invention
[0004] The present invention solves at least one of the problems of the related technologies from the following aspects.
[0005] In a first aspect of an embodiment of the present invention, a modified porous polymer membrane is provided, and the surface of the modified porous polymer membrane is modified with a compound of formula I. Wherein R is n is 200 - 2000.
[0006] Wherein the porous polymer membrane is selected from: porous polyethylene membrane, porous polyarylether membrane, porous polypropylene membrane, porous polyvinyl fluoride membrane, porous polyvinylidene fluoride membrane.
[0007] In some embodiments, the porous polymer membrane is a porous polytetrafluoroethylene membrane.
[0008] In a second aspect of an embodiment of the present invention, a preparation method of the porous polymer membrane according to any embodiment of the first aspect is provided, including: performing plasma treatment on the polymer membrane; and contacting the plasma-treated polymer membrane with a reaction solution containing 2-(methacryloyloxy)ethyl phosphorylcholine and a radical initiator for surface modification.
[0009] In some embodiments, the plasma treatment of the polymer membrane includes: contacting the polymer membrane with an acidic solution for pretreatment; and subjecting the pretreated polymer membrane to plasma treatment at a power of 10 - 50 W, a frequency of 1 - 16 MHz, and a time of 1 - 10 s, wherein the acidic solution is ethanol, acetic acid, and water with a mass ratio of (2 - 4):(0.5 - 1.5):(0.5 - 1.5).
[0010] In some embodiments, the radical initiator is selected from: azobisisobutyronitrile, diacyl peroxide, ammonium persulfate, cumene hydroperoxide.
[0011] In some embodiments, the contacting of the plasma - treated polymer membrane with a reaction solution containing 2 - (methacryloyloxy)ethyl phosphorylcholine and a radical initiator for surface modification includes: contacting a reaction solution containing 0.05 - 0.5 g / mL of 2 - (methacryloyloxy)ethyl phosphorylcholine and 0.005 - 0.05 g / mL of the radical initiator with the plasma - treated polymer membrane at 70 - 90 °C for 3 - 5 hours for surface modification.
[0012] The embodiments of the third aspect of the present invention provide a composite proton - exchange membrane, comprising: the modified polymer membrane as described in any embodiment of the first aspect and a perfluorosulfonic acid resin membrane, or the modified polymer membrane obtained by the preparation method as described in any embodiment of the second aspect and a perfluorosulfonic acid resin membrane.
[0013] Compared with the related art, the embodiments of the present application at least achieve the following beneficial effects:
[0014] The embodiments of the present application use a specific modifying compound, 2 - (methacryloyloxy)ethyl phosphorylcholine (MPC), to modify the porous polymer membrane, significantly changing its surface properties and the effect of its composite with the perfluorosulfonic acid resin membrane.
[0015] This modification method is simple and easy to implement and is easy to industrialize.
[0016] The strength of the composite proton - exchange membrane prepared by using the MPC - modified porous polymer membrane and perfluorosulfonic acid resin in the embodiments of the present application is greater than 63 Mpa, the elongation at break is greater than 80%, and the conductivity is greater than 0.102 S / cm, which is superior to the imported Gore proton - exchange membrane and has broad application prospects in the field of proton - exchange membranes. Description of the Drawings
[0017] Figure 1 It is the SEM image of the surface of the unmodified ePTFE membrane.
[0018] Figure 2 It is the SEM image of the surface of the modified ePTFE membrane 5 in Example 1.
[0019] Figure 3 The contact angle detection result of the unmodified ePTFE membrane and the aqueous solution.
[0020] Figure 4 The contact angle detection result of the modified ePTFE membrane 5 and the aqueous solution in Example 1.
[0021] Figure 5 The cross-sectional SEM image of the composite proton exchange membrane 5 in Example 2. Detailed Description of the Invention
[0022] The present invention will be further described in detail below in conjunction with the specific embodiments. The provided embodiments are only for clarifying the present invention and do not limit the scope of the present invention. The following provided embodiments can be used as a guide for those of ordinary skill in the art to make further improvements, and do not limit the present invention in any way.
[0023] Fuel cells are not limited by the Carnot efficiency compared to ordinary engines, so they are one of the competitors to replace internal combustion engines. PEM is a key component of proton exchange membrane fuel cells, and its essence is a perfluorosulfonic acid (PFSA) polymer membrane. This is because perfluorosulfonic acid (PFSA) has a high proton diffusion rate and good durability, so it is used to make PEM.
[0024] Currently, the most representative product in the world is DuPont Nafion membrane. However, DuPont also faces the problem that when the ion conductivity temperature of the PFSA membrane is higher than 80 °C, the membrane begins to lose moisture and gradually dries out, resulting in a rapid decline in the conductivity of PFSA. Therefore, improving the high-temperature and low-humidity electrochemical performance of PFSA membranes is an urgent problem that scientists need to solve. Some people add wet inorganic fillers such as zirconia or titania to the polymer to maintain its water content; some people develop partially fluorinated or non-fluorinated polymer membranes to replace perfluorosulfonic acid membranes; some people develop ultra-thin membranes; some people use polytetrafluoroethylene microporous membranes (ePTFE membranes) as the skeleton to mechanically enhance the proton membrane. However, among various methods to improve the performance of PEM currently, enhancing the PFSA / PTFE composite membrane is considered to be a most promising strategy. This composite structure can effectively reduce the material cost, reduce PFSA ion monomers, improve the mechanical strength, and at the same time exhibit fuel cell performance comparable to the original membrane, such as low proton resistance and high wettability at low relative humidity (RH) [1-2]. However, the incompatibility of hydrophilic ionomers in extremely hydrophobic ePTFE substrates and the severe volume change of PFSA, that is, repeated swelling / shrinking under wet / dry conditions, lead to interfacial defects and promote creep deformation. In particular, cracks, tears, voids, and delamination are mainly formed between the PTFE and PFSA layers, resulting in irreversible deterioration of fuel cell performance.
[0025] The hydrophilicity of the polymer surface is extremely important for the contact of different polymers. Ion irradiation and plasma treatment combined with subsequent surface chemical modification are usually used to achieve superhydrophilicity, especially for non-polar or weakly polar polymers such as polyetheretherketone (PEEK), polymethyl methacrylate (PMMA), polystyrene, polyethylene terephthalate, polycarbonate, polyimide, and polyvinylidene fluoride.
[0026] The inventors of this application unexpectedly found that modifying the surface of the ePTFE membrane with 2-(methacryloyloxy)ethyl phosphorylcholine (MPC) polymer significantly improved the hydrophilicity of the ePTFE membrane, thereby reducing the contact angle with PFSA, improving problems such as deformation between the resin and the ePTFE layer in the PEM, and enhancing the electrochemical durability and mechanical strength of the PEM.
[0027] In the related art, CN114369276A discloses a hydrophilic modified ePTFE membrane for fuel cell membranes and its preparation method. This patent sequentially performs ultrasonic treatment and silicic acid acidification to expose a large number of hydrophilic Si-OH groups on the surface of the ePTFE membrane, and then immerses the obtained silicic acid acidified ePTFE membrane in a fluorosulfonate solution with a certain concentration, so that the hydroxyl hydrophilic bond and the sulfonic acid group in the fluorosulfonate polymer are further combined through intermolecular hydrogen bonds to obtain an ePTFE membrane with better hydrophilic performance. The whole process is complex, with low scalability and limited material availability.
[0028] CN109092085A discloses that after acetone liquid suction, ultrasonic rinsing, and water pressing and drying, a graft-modified base membrane is obtained; then the graft-modified base membrane is immersed in a graft-modifying solution in a light-tight chamber under an inert gas environment, and then enters an ultraviolet irradiation chamber after being watered by a water spraying device in the chamber. After ultraviolet irradiation, a novel polytetrafluoroethylene hydrophilic modified membrane is obtained. The whole process is very complex, a large amount of inert gas is used, and the mechanical strength of the ePTFE membrane decreases due to multiple ultraviolet treatments of the ePTFE membrane.
[0029] In the enhanced composite proton exchange membrane, although using ePTFE as the reinforcement layer can bring many advantages, such as low proton internal resistance, high heat / mechanical stability, and low material cost. However, the negative effects cannot be ignored. For example, the incompatibility between the hydrophilic perfluorosulfonic acid resin and the hydrophobic PTFE substrate will cause obvious volume changes of PFSA when the battery cycles under wet and dry conditions. It swells under high humidity conditions and shrinks under dry conditions, so cracks will occur between the PTFE and PFSA layers. In more serious cases, tearing may cause contact between H2 and O2 during the battery cycle, resulting in an explosion, greatly reducing the stability of the PEM.
[0030] An embodiment of the present application provides a method for modifying an ePTFE membrane. The ePTFE membrane is treated with ultraviolet light to make the membrane carry active groups, and then 2-methacryloyloxyethyl phosphorylcholine (MPC) is fixed on the surface of the ePTFE membrane. The hydrophilicity of MPC is utilized to modify the ePTFE membrane, and then it is contacted with PFSA resin to produce a proton membrane with high strength and high stability. This method is simple, the applicable width of the bottom membrane is large, and it is cheap and efficient in the use process.
[0031] An embodiment of the first aspect of the present invention provides a modified porous polymer membrane, and the surface of the modified porous polymer membrane is modified with a compound of formula I. Wherein R is n is an integer from 200 to 2000 (any integer in 200 - 2000, such as 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1050, 1100, 1150, 1200, 1250, 1300, 1350, 1400, 1450, 1500, 1550, 1600, 1650, 1700, 1750, 1800, 1850, 1900, 1950, 2000).
[0032] Wherein the porous polymer membrane is selected from: porous polyethylene membrane, porous polyarylether membrane, porous polypropylene membrane, porous polyvinyl fluoride membrane, porous polyvinylidene fluoride membrane.
[0033] It can be understood that the first end of the compound of formula I is connected to the porous polymer membrane, and the second end of the compound of formula I is connected to an H atom.
[0034] In some embodiments, the first end of the compound of formula I is connected to the porous polymer membrane through an oxygen atom, and the second end of the compound of formula I is connected to an H atom.
[0035] In some embodiments, the porous polymer membrane is a porous polytetrafluoroethylene membrane.
[0036] An embodiment of the second aspect of the present invention provides a method for preparing the porous polymer membrane according to any one of the above embodiments of the first aspect, including: performing plasma treatment on the polymer membrane; and contacting the plasma-treated polymer membrane with a reaction solution containing 2-(methacryloyloxy)ethyl phosphorylcholine and a radical initiator for surface modification.
[0037] The structural formula of the compound 2-methacryloyloxyethyl phosphorylcholine (MPC) used is as follows:
[0038]
[0039] In the embodiments of the present application, the ePTFE membrane is treated in an atmospheric environment with Plasma at an appropriate power to activate its surface. Plasma treatment is crucial for the surface activation of the ePTFE membrane because it can break the inert C-F chemical bonds on the ePTFE surface and generate active groups such as -H, -OH, and -O. These functional groups increase the wettability of the monomer aqueous solution. More importantly, they can serve as primer groups for free radical polymerization covalent grafting. Then, MPC is grafted onto the surface of the ePTFE membrane treated with plasma by spraying or solution infiltration. The above reaction is convenient and simple to carry out in a water bath or at a lower temperature. The free radical initiator is generally selected from azobisisobutyronitrile, diacyl peroxide, ammonium persulfate, or cumene hydroperoxide, etc. After grafting MPC on the surface of the ePTFE membrane, the contact angle with the PFSA resin can be greatly reduced, the strength of the composite ion exchange membrane can be improved, its conductivity can be enhanced, and the comprehensive performance can be promoted. With the improvement of the compatibility between the reinforcing layer and the ion exchange resin, the PEM composite membrane based on the modified porous polymer membrane of the embodiments of the present application has a high packing density and high strength, and is more suitable for application in fuel cell proton exchange membranes.
[0040]
[0041] In some embodiments, the plasma treatment of the polymer membrane includes: contacting the polymer membrane with an acidic solution for pretreatment; and performing plasma treatment on the pretreated polymer membrane at a power of 10 - 50 W (such as 15 W, 20 W, 25 W, 30 W, 35 W, 40 W, 45 W, 50 W), a frequency of 1 - 16 MHz (such as 2 MHz, 3 MHz, 4 MHz, 5 MHz, 6 MHz, 7 MHz, 8 MHz, 9 MHz, 10 MHz, 11 MHz, 12 MHz, 13 MHz, 14 MHz, 15 MHz, 16 MHz), and a time of 1 - 10 s (such as 3 s, 4 s, 5 s, 6 s, 7 s, 8 s, 9 s, 10 s), wherein the acidic solution is ethanol, acetic acid, and water with a mass ratio of (2 - 4):(0.5 - 1.5):(0.5 - 1.5) (such as 2.5:0.5:0.5, 3:0.5:0.5, 3.5:0.5:0.5, 2.5:1:0.5, 3:1:0.5, 3.5:1:0.5, 2.5:1.5:0.5, 3:1.5:0.5, 3.5:1.5:0.5, 2.5:0.5:1, 3:0.5:1, 3.5:0.5:1, 2.5:1:1, 3:1:1, 3.5:1:1, 2.5:1.5:1.5, 3:1.5:1.5, 3.5:1.5:1.5).
[0042] In some embodiments, the free radical initiator is selected from: azobisisobutyronitrile, diacyl peroxide, ammonium persulfate, cumene hydroperoxide.
[0043] In some embodiments, the surface modification by contacting a reaction solution containing 2-(methacryloyloxy)ethyl phosphorylcholine and a radical initiator with a plasma-treated polymer membrane includes: contacting a reaction solution containing 0.05 - 0.5 g / mL (such as 0.06 g / mL, 0.07 g / mL, 0.08 g / mL, 0.09 g / mL, 0.1 g / mL, 0.15 g / mL, 0.2 g / mL, 0.25 g / mL, 0.3 g / mL, 0.35 g / mL, 0.4 g / mL, 0.45 g / mL, 0.5 g / mL) of 2-(methacryloyloxy)ethyl phosphorylcholine and 0.005 - 0.05 g / mL (such as 0.006 g / mL, 0.007 g / mL, 0.008 g / mL, 0.009 g / mL, 0.01 g / mL, 0.011 g / mL, 0.012 g / mL, 0.013 g / mL, 0.014 g / mL, 0.015 g / mL, 0.016 g / mL, 0.017 g / mL, 0.018 g / mL, 0.019 g / mL, 0.02 g / mL, 0.025 g / mL, 0.03 g / mL, 0.035 g / mL, 0.04 g / mL, 0.045 g / mL, 0.05 g / mL) of a radical initiator with the plasma-treated polymer membrane at 70 - 90 °C (such as 71 °C, 72 °C, 73 °C, 74 °C, 75 °C, 76 °C, 77 °C, 78 °C, 79 °C, 80 °C, 81 °C, 82 °C, 83 °C, 84 °C, 85 °C, 86 °C, 87 °C, 88 °C, 89 °C, 90 °C) for 3 - 5 hours (such as 3.5 hours, 4 hours, 4.5 hours, 5 hours) for surface modification.
[0044] An embodiment of the third aspect of the present invention provides a composite proton exchange membrane, comprising: a modified polymer membrane as described in any embodiment of the first aspect and a perfluorosulfonic acid resin membrane, or a modified polymer membrane obtained by the preparation method as described in any embodiment of the second aspect and a perfluorosulfonic acid resin membrane.
[0045] The following examples are used to further illustrate the advantages and characteristics of the present method, rather than limiting the present invention. The experimental methods in the following examples are all conventional methods, unless otherwise specified, and are carried out according to the techniques or conditions described in the literature in the art or according to the product specifications.
[0046] Unless otherwise specified, the quantitative analysis tests in the following examples are all set with three repeated experiments, and the results are averaged.
[0047] Example 1 Preparation of 2-(methacryloyloxy)ethyl phosphorylcholine modified ePTFE membrane
[0048] 1.1 Immerse the Gore (or Donaldson) ePTFE membrane in a solution of ethanol: acetic acid: water = 3:1:1 for 24 h, then wash it with deionized water in an ultrasonic machine, and then place it in an 80 °C oven to remove the residual solution. Repeat this process twice to obtain the pretreated ePTFE membrane.
[0049] 1.2 Plasma-treat the pretreated ePTFE membrane under the following conditions: Treat it in air with a power of 25 w for 6 s, and then expose it to air for 5 min.
[0050] 1.3 Weigh 10 g of 2-(methacryloyloxy)ethyl phosphorylcholine and 1 g of ammonium persulfate, dissolve them in 100 mL of water to prepare a solution containing 0.1 g / mL of 2-(methacryloyloxy)ethyl phosphorylcholine and 0.01 g / mL of ammonium persulfate. Spray it evenly on the plasma-treated ePTFE membrane prepared in step 1.2 by spraying, and let it polymerize at 80 °C for 4 h. Then wash it several times with deionized water and ethyl acetate respectively to finally obtain the 2-(methacryloyloxy)ethyl phosphorylcholine-modified ePTFE membrane (modified ePTFE membrane 1).
[0051] Perform SEM detection on the 2-(methacryloyloxy)ethyl phosphorylcholine-modified ePTFE membrane prepared in step 1.3. The detection results show that the fibers of this membrane are uniform in thickness, with few breakpoints and broken fibers, showing a significant improvement compared with the unmodified ePTFE membrane.
[0052] Example 2 Preparation of composite membrane
[0053] 2.1 Prepare perfluorosulfonic acid solution: Completely dissolve 3M perfluorosulfonic acid resin in a mixed solution of ethanol: water: isopropanol with a mass ratio of 5:2:3 to prepare a first-coating solution with a solid content of 9% and a viscosity of 90 mPa·s and a second-coating solution with a solid content of 25% and a viscosity of 80 mPa·s.
[0054] 2.2 First-coat the proton membrane: Set the scraping speed of the coater (Hefei Kejing) to 25 and the height of the scraper to 11 μm. Place the Daicel PET base film (cut into A4 paper size) on the coater, drop 10 mL of the first-coating solution prepared in step 2.1, start the equipment to scrape the resin solution evenly first, then cut the 2-(methacryloyloxy)ethyl phosphorylcholine-modified ePTFE membrane prepared in Example 1 into A4 size and cover it on the first-coating solution. Wait at room temperature for 5 min to allow the solution to completely infiltrate the 2-(methacryloyloxy)ethyl phosphorylcholine-modified ePTFE membrane, and then dry it at 60 °C for 20 min to remove it.
[0055] 2.3 Preparation of modified proton exchange membrane: Reset the height of the doctor blade to 8 μm, continue to drop 8 mL of the second coating solution on the membrane prepared in the above step 2.2, keep the speed of the doctor blade unchanged, scrape it again, and after completion, place it in an oven at 160 °C for heat preservation for 10 min to remove the solvent. In summary, the preparation of the composite proton exchange membrane based on the 2-(methacryloyloxy)ethyl phosphorylcholine modified ePTFE membrane is completed, and the composite proton exchange membrane 1 is obtained respectively.
[0056] Perform SEM detection on the composite proton exchange membrane 1 prepared in step 2.3. The results show that after the ePTFE membrane is grafted with 2-(methacryloyloxy)ethyl phosphorylcholine polymer, it is tightly filled with resin, improving the strength of the composite membrane.
[0057] Comparative Example 1
[0058] In the preparation of the modified ePTFE in this comparative example, it is basically the same as that in Example 1, except that sodium styrene sulfonate is used instead of 2-(methacryloyloxy)ethyl phosphorylcholine in this application to prepare the comparative modified ePTFE membrane 1.
[0059] Use the comparative modified ePTFE membrane 1 to prepare the comparative composite proton exchange membrane 1, and the preparation steps are the same as those in Example 2.
[0060] Comparative Example 2
[0061] In the preparation of the modified ePTFE in this comparative example, it is basically the same as that in Example 1, except that N,N-dimethylacetamide is used instead of 2-(methacryloyloxy)ethyl phosphorylcholine in this application to prepare the comparative modified ePTFE membrane 2.
[0062] Use the comparative modified ePTFE membrane 2 to prepare the comparative composite proton exchange membrane 2, and the preparation steps are the same as those in Example 2.
[0063] Detection Example
[0064] Perform mechanical property and conductivity detection on the modified ePTFE membranes prepared in each example. The results are shown in Table 1 below.
[0065] The mechanical properties are tested according to the standard of GB / T 1040-2006.
[0066] Conductivity: Use the electrochemical workstation Metrohm Autolab PGSTAT302N to measure the AC impedance of the thin film, calculate the proton conductivity, the AC frequency is 1-10 5 Hz, and the scanning amplitude is 10 mV. The clamping method of the thin film is based on the four-electrode method, and two types of customized clamps are used to measure the normal conductivity (σ⊥) and parallel conductivity (σ∥) of the membrane respectively.
[0067] Table 1
[0068]
[0069]
[0070] Table 2
[0071]
[0072] References:
[0073] [1] J.Shim, H.Y.Ha, S.A.Hong, I.H.Oh, J.Power Sources 2002, 109, 412;
[0075] [2] H.L.Tang, M.Pan, F.Wang, J.Appl.Polym.Sci. 2008, 109, 2671.
[0077] [3] Q.Shao, S.Jiang, Molecular understanding and design of zwitterionic materials, Adv.Mater. 27(1)(2015) 15–26.
[0079] [4] B.Wu, L.Zhang, L.Huang, S.Xiao, Y.Yang, M.Zhong, J.Yang, Salt-Induced regenerative surface for bacteria killing and release, Langmuir 33(28)(2017) 7160–7168.
[0082] [5] Y.Fu, Y.Wang, L.Huang, S.Xiao, F.Chen, P.Fan, M.Zhong, J.Tan, J.Yang, Salt responsive “killing and release” antibacterial surfaces of mixed polymer brushes, Ind.Eng.Chem.Res. 57(27)(2018) 8938–8945.
[0084] In the description of this specification, the descriptions referring to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples", etc. mean that the specific features, structures, materials, or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, without contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples.
[0085] Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those of ordinary skill in the art can make changes, modifications, substitutions, and variations to the above embodiments within the scope of the present invention.
Claims
1. A modified porous polymer membrane, characterized in that, The surface of the modified porous polymer membrane is modified with a compound of formula I, wherein R is n is from 200 to 2000, The porous polymer membrane is selected from: porous polyethylene membrane, porous polyarylether membrane, porous polypropylene membrane, porous polyvinyl fluoride membrane, and porous polyvinylidene fluoride membrane.
2. The modified porous polymer membrane according to claim 1, wherein The porous polymer membrane is a porous polytetrafluoroethylene membrane.
3. The method for preparing the porous polymer membrane according to claim 1 or 2, comprising: Performing plasma treatment on the polymer membrane; and Contacting the plasma-treated polymer membrane with a reaction solution containing 2-(methacryloyloxy)ethyl phosphorylcholine and a radical initiator for surface modification.
4. The preparation method according to claim 3, wherein The performing plasma treatment on the polymer membrane includes: Contacting the polymer membrane with an acidic solution for pretreatment; and Performing plasma treatment on the pretreated polymer membrane at a power of 10-50 W, a frequency of 1-16 MHz, and a time of 1-10 s, wherein the acidic solution is ethanol, acetic acid, and water with a mass ratio of (2-4):(0.5-1.5):(0.5-1.5).
5. The preparation method according to claim 3, characterized in that, wherein the radical initiator is selected from: azobisisobutyronitrile, diacyl peroxide, ammonium persulfate, and cumene hydroperoxide.
6. The preparation method according to claim 3, wherein The contacting the plasma-treated polymer membrane with a reaction solution containing 2-(methacryloyloxy)ethyl phosphorylcholine and a radical initiator for surface modification includes: Contacting a reaction solution containing 0.05-0.5 g / mL of 2-(methacryloyloxy)ethyl phosphorylcholine and 0.005-0.05 g / mL of a radical initiator with the plasma-treated polymer membrane at 70-90 °C for 3-5 hours for surface modification.
7. A composite proton exchange membrane, characterized in that, Comprising: The modified polymer membrane and the perfluorosulfonic acid resin membrane according to claim 1 or 2, or The modified polymer membrane and the perfluorosulfonic acid resin membrane obtained by the preparation method according to any one of claims 3 to 6.
Citation Information
Patent Citations
Photo-induced polytetrafluoroethylene hydrophilic modification method
CN109092085A